“They looked German, albeit with even tighter pants and uglier shoes, but there was something different about them”: The Function of East and West Germany and the Fall of the Berlin Wall in Paul Beatty’s Slumberland - Schweinfurth, Elisa (Current Objectives of Postgraduate American Studies, 2012)
The essay examines Paul Beatty’s novel Slumberland“ (2008) as representative for a still neglected field of American literary expression: American literary representations of Germany after 1989 which address issues of Germany’s former division into East and West, the fall of the Berlin Wall, and German reunification. It argues that the function of the German setting is not used to affirm a U.S. American identity through the othering of Germany but that it critically addresses controversial issues in the United States through the use of displacement.